Studi Parametrik Mortar Geopolimer Hybrid Abu Sawit (Palm Oil Fuel Ash/POFA) - Yanuari, Ramadhan; Ikrammullah, Muhammad; Septari, Dinda; Wijaya, Miguel Felix; Olivia, Monita (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2020)
In this study, the Palm Oil Fuel Ash (POFA) was used as a raw material for making geopolymer mortars that uses a combination of sodium hydroxide (NaOH) and sodium silicate (Na2SiO3). The purpose of this study was to determine the effect of various parameters on the compressive strength of mortars. The parameters involved were namely modulus of activator ratio (Ms 1-3), the molarity of NaOH (10-16M), curing temperature (28-110ÂºC), type of POFA particle processing (oven-dried, passed the #200 sieve, burned in a brick kiln, burned at 800ÂºC), rest periods of 3 and 5 days. Based on the parametric study, it was found the optimum mixture with the highest compressive strength consisted of NaOH 14M, Ms ratio of 2.5, curing temperature of 100OC, a rest period of 5 days, particles sieved using #200 sieve and had 15% PCC content.Â